High-quality histochemistry, immunohistochemistry, and immunofluorescence on xylene- and formalin-free paraffin-embedded tissues - Maarten Niemantsverdriet; Anne Mei Eshuis; Naomi van der Horst; Rory Ogink; Pien van Smeerdijk; Jose van der Starre-Gaal; Agnes Marije Hoogland (PLoS ONE, 2026)
Pathology is a vital part of modern medicine, playing an essential role in disease diagnosis, prognosis, and therapy choice. The field of pathology depends on traditional tissue embedding techniques, still routinely using toxic and even carcinogenic substances to process tissues for diagnostics. Chronic exposure of humans to xylene and/or formalin, two essential components in the process, may result in severe health problems. Accumulating insights resulted in a ban of formalin in Europe for multiple applications and tight restrictions for almost all other uses since its toxicity levels were upgraded to carcinogen grade 1B and mutagen grade 2. A remarkable exception to these regulations is the use of formalin in the field of pathology, because of the existing lack of formalin-free tissue embedding methods that produce high-quality pathology specimens. Here we show that a novel embedding technique employing supercritical Carbon dioxide (CO 2 ), used in a xylene- and formalin-free manner, results in high-quality tissue samples, suitable for the fundamental techniques used in pathology: histochemistry, immunohistochemistry, and immunofluorescence.